2012
DOI: 10.1128/iai.05684-11
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Ovine Antibody-Based Platform for Treatment of Clostridium difficile Infection

Abstract: Treatment of Clostridium difficile is a major problem as a hospital-associated infection which can cause severe, recurrent diarrhea. The currently available antibiotics are not effective in all cases and alternative treatments are required. In the present study, an ovine antibody-based platform for passive immunotherapy of C. difficile infection is described. Antibodies with high toxin-neutralizing titers were generated against C. difficile toxins A and B and were shown to neutralize three sequence variants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 40 publications
3
39
0
1
Order By: Relevance
“…Although animals immunized with peptides produced high serum titers (typically 1:100,000), neutralizing antibodies could not be isolated. Animals which had been crosstoxin immunized and screened produced a small number of crossreactive MAbs, none of which demonstrated neutralizing activity, consistent with previous observations (34,41). Together with the results of analysis of sequence alignments, these data suggested that it was not possible to identify MAbs which potently neutralized both TcdA and TcdB.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Although animals immunized with peptides produced high serum titers (typically 1:100,000), neutralizing antibodies could not be isolated. Animals which had been crosstoxin immunized and screened produced a small number of crossreactive MAbs, none of which demonstrated neutralizing activity, consistent with previous observations (34,41). Together with the results of analysis of sequence alignments, these data suggested that it was not possible to identify MAbs which potently neutralized both TcdA and TcdB.…”
Section: Resultssupporting
confidence: 76%
“…Parenteral administration of purified antibodies offers control over both timing and dose. The manufacture of colostrum or serum polyclonal antibodies from cow, sheep, chicken, and alpaca or other species for therapeutic use can have production quality difficulties in controlling the variability of batch-to-batch antitoxin activities (titer and specificity) and the total production capacity, and there can be immunogenicity concerns (24,25,(30)(31)(32)(33)(34). The use of mixtures of monoclonal antibodies offers an advantage over polyclonal sera in these respects.…”
mentioning
confidence: 99%
“…Passive immunization strategies have focused on the use of toxin-specific antibodies, including humanised monoclonal antibodies, 45 alpaca 41 and ovine-derived antibodies, 46 as well as bovine hyperimmune colostrum. 47 In addition, a number of active vaccination strategies targeting the toxins are under development.…”
Section: The Large Glucosylating Toxins Tcda and Tcdbmentioning
confidence: 99%
“…Ha a fenti tények még nem lennének elegendőek a jelenlegi klinikai gyakorlat globális átértékeléséhez, további fenyegetést jelent, hogy a CDiff fertőzések kezelésére egyre gyakrabban alkalmazott vancomycin per os használta vancomycin-rezisztens Enterococcus (VRE) megjelenésével és ezen törzsekből transconjugatióval, a már hazánkban is leírt, vancomycin-methicillin-rezisztens Staphylococcus aureus (VMRSA) kialakulásával fenyeget [6,7,8]. Nem meglepő, hogy világszerte történnek próbálkozások alternatív kezelési, megelőzési és infekció kontroll stratégiák kidolgozására [9,10,11,12,13]. Ezen alternatív eljárások közül egyelőre egyedül a széklettranszplantáció vagy más néven faecalis bacteriotherápia kezd nemzetközileg elterjedni, elsősorban a beavatkozással elérhető kiváló gyógyulási ráta (≈92%) és alacsony recidíva arány (≈6%), másodsorban pedig relatív egyszerűsége, biztonságossága és költséghatékonysága miatt [14,15].…”
Section: Discussionunclassified